2019
DOI: 10.1186/s12887-019-1699-9
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone addiction may be associated with adolescent hypertension: a cross-sectional study among junior school students in China

Abstract: Background Hypertension in children and adolescents is on the rise worldwide, especially in China. The prevalence of hypertension is related to many factors, such as obesity. In the era of smart phones, it is important to study the negative health effects of mobile phones on blood pressure. The purpose of this study was to investigate the prevalence of hypertension and its association with smartphone addiction among junior school students in China. Methods A school-base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
55
2
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 54 publications
(66 reference statements)
4
55
2
5
Order By: Relevance
“…In addition, advertisements for food products, to which students might be exposed via ST device use, could increase children’s preferences for such products and eventually increase purchases of them [ 15 ]. In addition, a study in China found that addiction to smartphone device use among children could be a predictive factor for hypertension and obesity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, advertisements for food products, to which students might be exposed via ST device use, could increase children’s preferences for such products and eventually increase purchases of them [ 15 ]. In addition, a study in China found that addiction to smartphone device use among children could be a predictive factor for hypertension and obesity [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Pesquisadores chineses associaram a dependência do telefone celular pelos adolescentes com a má qualidade do sono, a obesidade e a hipertensão. Concluíram que o uso do smartphone está associado à privação e má qualidade do sono, à pressão arterial elevada e ao risco de doenças cardiovasculares na idade adulta (33,34).…”
Section: Discussionunclassified
“…Compared with older people, children and young adults have greater risks of the undesirable consequences of smartphone overuse because they have less self-control in smartphone use [ 11 ]. A cross-sectional study (N=2639 participants) indicated that 22.8% of teenagers were addicted to smartphone use, which was related to hypertension [ 16 ]. Another study showed that users of mobile devices spent >20 hours weekly on email, text messages, and social networking services, indicating the heavy reliance on smartphones in their communication with other people [ 17 ].…”
Section: Introductionmentioning
confidence: 99%